Analysis of Habituation in Implementing the Merdeka Belajar Curriculum in Art Education in Schools - Heriyati Yatim; Jamilah Jamilah; Nurachmy Sahnir; Amirullah Abduh (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
The implementation of the Merdeka Curriculum in art education presents its own challenges. Therefore, good habituation from teachers, schools, and students is needed, as well as preparedness and awareness in understanding and interpreting the implementation of the Merdeka curriculum in a student-focused learning process. The aim of this research is to raise teachers' awareness of the importance of understanding and implementing the Merdeka Curriculum with differentiated learning to support the development of students' character. A qualitative method was used with interviews, observations, and literature study documentation to collect data from leading schools, leading teachers, and learning committee supervisors. Data analysis was conducted to extract themes relevant to the habituation of implementing the Merdeka Belajar Curriculum in art education to improve active, independent, and creative learning, as well as improving the quality of human resources (HR) with facility infrastructure in schools. The research results are expected to contribute to optimizing the implementation of the Merdeka curriculum in schools for the development of innovative and creative art education teachers who liberate students, as well as improving students' abilities in the field of art to support the profile of Pancasila students.